Nano twin crystal copper patch antenna and preparation method thereof

By preparing copper antennas with nanotwin structures and using pulse electrodeposition technology, combined with the design of dielectric substrate and protective layer, the shortcomings of existing microstrip patch antennas in terms of flexibility, ultra-thin and high integration are solved, and the high conductivity, mechanical performance and radio frequency performance of nanotwin copper patch antennas are improved.

CN119627404AActive Publication Date: 2025-03-14WUHAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411640920.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-14
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

Existing microstrip patch antennas have shortcomings in flexibility, ultra-thinness and high integration, especially in the case of high shape complexity, in terms of mechanical properties and manufacturing process complexity.

Method used

By preparing a copper antenna with a nanotwin structure and using pulse electrodeposition technology to make it into a nanotwin copper patch antenna, combined with the design of a dielectric substrate and protective layer, the conductivity, radio frequency performance and mechanical properties of the antenna are improved.

Benefits of technology

The high conductivity and mechanical performance improvement of nanotwin copper patch antenna is achieved, and at the same time, it shows good frequency band response and anti-interference ability in the 5.25GHz frequency band, and the signal transmission loss is less than 10dB.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627404A_ABST
    Figure CN119627404A_ABST
Patent Text Reader

Abstract

The invention discloses a nano-twin copper patch antenna and a preparation method thereof, and relates to the field of micro electro-mechanical devices, the nano-twin copper patch antenna comprises a nano-twin copper antenna, a dielectric substrate and a protective layer covering the nano-twin copper antenna, the thickness of the nano-twin copper antenna is 0.1-200 [mu] m, and the organization structure of the nano-twin copper antenna comprises a nano-twin structure. The nano-twin copper antenna with the organization structure containing the nano-twin structure is prepared, and the conductivity, the radio frequency performance and the mechanical performance of the nano-twin copper patch antenna are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of micro-electromechanical devices, and in particular to a nano-twin copper patch antenna and a preparation method thereof. Background Art

[0002] Today's world is a world of rapid information development. 5G technology, Internet of Things (IoT) technology and other technologies are booming. Mobile communication devices are increasingly evolving towards wearable and portable directions, which puts higher requirements on flexible, ultra-thin and highly integrated wireless communication components. Fields such as life health monitoring and portable radio frequency tags have already had extremely strong demands for flexible and ultra-thin wireless communication components. How to manufacture wireless communication components that can meet the needs of flexibility and ultra-thinness while ensuring good radiation performance of the components has extremely broad research prospects. There has been very in-depth research in the field of microstrip patch antennas. Traditional high-performance microstrip patch antennas are designed based on traditional high-conductivity metals (such as copper, silver, gold, aluminum, etc.) and have been widely used in fields such as satellite communications, remote sensing detection, and mobile devices.

[0003] Microstrip patch antennas with high shape complexity are often produced by printing and other methods due to their delicate structure. The processing procedures are complicated, a large number of equipment are required, and the manufacturing cost is high. However, for integrated microstrip RF devices or conformal microstrip antennas with high shape complexity, the application of metal materials is severely limited by their low flexibility and complex manufacturing process. To solve this problem, current research focuses on changing the metal morphology to improve mechanical properties, mainly including metal mesh, liquid metal and metal ink. However, liquid metal has low conductivity due to its surface oxide, and the additives in the metal ink make its conductivity less than ideal, which reduces the performance of the prepared patch antenna during use. Summary of the invention

[0004] In view of the shortcomings of the above-mentioned related technologies, the present application provides a nano-twinned copper patch antenna and a preparation method thereof. The present application improves the conductivity, radio frequency performance and mechanical properties of the copper patch antenna by preparing a copper antenna with a nano-twinned structure.

[0005] In the first aspect, the present application provides a nano-twin copper patch antenna adopting the following technical solution: A nano-twin copper patch antenna comprises a nano-twin copper antenna, a dielectric substrate and a protective layer covering the nano-twin copper antenna, wherein the thickness of the nano-twin copper antenna is 0.1-200 μm, and the organizational structure of the nano-twin copper antenna comprises a nano-twin structure.

[0006] Preferably, the twin spacing of the nano-twin structure is 10-500 nm.

[0007] Preferably, the dielectric constant of the dielectric substrate is 2-6 and the thickness is 0.5-2 mm.

[0008] Preferably, the dielectric substrate comprises one or more of polyethylene terephthalate, polydimethylsiloxane and epoxy glass fiber composite material.

[0009] Preferably, considering economy, practicality and thermal stability at high frequencies, a 0.5 mm thick polytetrafluoroethylene plate (with a dielectric constant of 2) is used as the dielectric substrate.

[0010] In a second aspect, the present application provides a method for preparing a nano-twin copper patch antenna using the following technical solution: A method for preparing a nano twin copper patch antenna comprises the following steps: placing a nano twin copper anode and a cathode plate in an electroplating solution containing sulfuric acid nano twin copper, constructing an electrolyte channel between the cathode plate and the anode, applying a pulse current through the anode and the cathode plate and moving the anode relative to the cathode plate to perform electrodeposition on the cathode plate, thereby obtaining a nano twin copper antenna; The nano-twin copper antenna is removed from the cathode plate, cleaned, and fixed to a dielectric substrate, and then a protective layer covering the antenna is fixed on the dielectric substrate to obtain the nano-twin copper patch antenna.

[0011] Preferably, the electroplating solution comprises copper sulfate, polyethylene glycol, an emulsifier and sodium chloride, the concentration of the copper sulfate is 0.1-1M, the concentration of the polyethylene glycol is 0.05-0.1 g / L, the concentration of the emulsifier is 0.05-0.1 g / L, and the concentration of the sodium chloride is 0-100 mg / L.

[0012] Preferably, the electroplating solution further comprises a brightener, a leveler and a dispersant, the concentration of the brightener is 0.01-0.1 g / L, the concentration of the leveler is 0.01-0.1 g / L, and the concentration of the dispersant is 0.01-0.1 g / L.

[0013] Preferably, the electrolyte further comprises an oxidant, wherein the oxidant is 27.5-35wt% hydrogen peroxide, and the addition amount is 1-10mL / L.

[0014] Preferably, the pH of the electroplating solution is not greater than 1.

[0015] Preferably, the voltage of the pulse current is 10-50V, and the current density is 30-200mA / cm 2 , the turn-on time is 10-50ms, and the turn-off time is 100-300ms.

[0016] In summary, the present application includes at least one of the following beneficial technical effects: 1. This application improves the conductivity and mechanical properties of the nano-twin copper patch antenna by preparing a nano-twin copper antenna with a nano-twin structure.

[0017] 2. The nano-twin copper patch antenna prepared in this application has good frequency response in the 5.25GHz frequency band, signal transmission loss is less than 10dB, and has strong anti-interference ability, thereby improving the RF performance of the nano-twin copper patch antenna.

[0018] 3. The present application prepares a nano-twin copper antenna by pulse electrodeposition, and makes the nano-twin copper antenna into a nano-twin copper patch antenna, which is beneficial to improving the controllability of the organizational structure of the nano-twin copper antenna, and is beneficial to the organizational structure of the nano-twin structure within the nano-twin copper antenna, thereby improving the electrical conductivity and mechanical properties of the nano-twin copper patch antenna. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a physical picture of the copper antenna of Example 1 of the present application; Figure 2 is a physical picture of the copper antenna of Example 2 of the present application; Figure 3 is a transmission electron microscope image of the copper antenna of Example 1 of the present application; Figure 4 is the S of the copper patch antenna of Example 2 of the present application 11 Performance graphs; Figure 5 It is a comparison chart of the hardness of the copper antennas of Comparative Example 1 and Example 1 of the present application. DETAILED DESCRIPTION

[0020] The present application is further described in detail below in conjunction with examples. The following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. In the following examples, if specific conditions are not specified, they are carried out according to normal conditions or conditions recommended by the manufacturer. The methods used are conventional methods known in the art unless otherwise specified, and the consumables and reagents used are commercially available unless otherwise specified. Unless otherwise specified, the professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the recorded content may also be applied to the present invention.

[0021] The raw materials used in the examples and comparative examples can all be obtained commercially.

[0022] Example 1 Embodiment 1 of the present application provides a nano-twinned copper patch antenna, and its preparation method is as follows: (1) prepare a basic electroplating solution with a sulfuric acid nano-twinned copper concentration of 0.5 mol / L, a polyethylene glycol concentration of 0.07 g / L, an emulsifier concentration of 0.07 g / L, a sodium chloride concentration of 50 mg / L, a brightener concentration of 0.05 g / L, a leveler concentration of 0.05 g / L, and a dispersant concentration of 0.05 g / L, add 30 wt% hydrogen peroxide to the basic electroplating solution at a ratio of 5 ml / L, and adjust the pH to 1 with sulfuric acid to obtain an electroplating solution and add it to a plating tank.

[0023] (2) Nano-twinned copper metal is used as the anode and stainless steel plate is used as the cathode plate. The anode is installed in a nozzle filled with electroplating solution, and the cathode plate is installed in a plating solution tank. The electroplating solution in the nozzle is controlled to flow into the plating solution tank through the nozzle. An electrolyte channel is constructed between the cathode plate and the anode. A pulse current is applied through the anode and cathode plates. The voltage of the pulse current is: 10V, and the current density is 200mA / cm 2 , the conduction time is 20ms, the disconnection time is 100ms, and the anode is moved in a serpentine shape relative to the cathode plate to perform electrodeposition on the cathode plate, and a serpentine-shaped nano-twin copper antenna with a thickness of 20μm is obtained, such as Figure 1 As shown; (3) The nano-twin copper antenna is removed from the cathode plate and rinsed with alcohol and water, then pasted to one side of the dielectric substrate and a ground layer is pasted on the other side, polyimide tape is used to cover the nano-twin copper antenna and pasted to the dielectric substrate to form a protective layer, thereby obtaining the nano-twin copper patch antenna. When in use, the nano-twin copper patch antenna is connected to the antenna terminal by conductive glue or welding.

[0024] Example 2 Example 2 of the present application provides a nano-twin copper patch antenna. The difference between Example 2 and Example 1 is that during the preparation process of Example 2, the nano-twin copper antenna is formed into a star shape, and its thickness is: 30 μm, such as Figure 2 shown.

[0025] Comparative Example 1 Comparative Example 1 provides a method for preparing a coarse-grained copper patch antenna, and the preparation method is as follows: a coarse-grained copper wire is used and pressed into shape by a mold to prepare a coarse-grained copper antenna with the same shape and thickness as Example 1.

[0026] Test and Inspection The copper antenna of Example 1 was imaged by transmission electron microscopy. Figure 3 The S11 performance diagram of the copper patch antenna of Example 2 is measured, as shown in FIG. Figure 4As shown, the horizontal axis represents the signal frequency band, and the vertical axis represents the frequency band loss. The hardness of the copper antenna of comparative example 1 and embodiment 1 is detected, and the hardness comparison diagram of the copper antenna of comparative example 1 and embodiment 1 is obtained as shown in Figure 5 Results Analysis The following combination Figure 1-5 The experimental results provided are used to explain this application in detail.

[0027] Reference Figure 1 and Figure 2 The width of the nano-twin copper antenna in Example 1 and Example 2 is about 500 μm, and the width is uniform, the outline is clear, and the size is accurate, indicating that the present application prepares the nano-twin copper patch antenna by configuring the electroplating solution and adopting the electrodeposition method, which is beneficial to improving the molding effect and dimensional accuracy of the nano-twin copper antenna with a micron-level structure.

[0028] Reference Figure 3 It can be seen that the nano-twin copper antenna in the nano-twin copper patch antenna of Example 1 of the present application has a high-density twin structure in its organizational structure, and its twin spacing is: 50-100nm, indicating that the preparation method of the nano-twin copper patch antenna of the present application can successfully prepare a nano-twin copper antenna containing a twin structure, and the hindering effect of the twin boundary on the dislocation movement can be regarded as an internal obstacle to the dislocation movement. This effect is similar to the strengthening effect of the grain boundary, thereby improving the strength of the material. As a special coherent grain boundary, the grain boundary has an order of magnitude less scattering ability for electrons than conventional grain boundaries. This means that obtaining a high-density twin boundary in a metal may effectively improve the strength of the metal while having little effect on its conductive properties. In the study of nano-twin nano-twin copper, it was found that the increase of twin boundaries can significantly improve the strength and tensile plasticity of the material, while the conductivity is almost unchanged, which is equivalent to oxygen-free high-conductivity nano-twin copper. While improving the mechanical strength of the nano-twin copper patch antenna, it also improves the RF performance of the nano-twin copper patch antenna. .

[0029] Reference Figure 4 It can be seen that the horizontal coordinate corresponding to the minimum frequency band loss of the nano-twin copper patch antenna in Example 2 of the present application is 5.25 GHz, that is, the nano-twin copper patch antenna in Example 2 of the present application has a good frequency band response in the 5.25 GHz band, and the signal transmission loss is less than 10 dB, and has the characteristics of narrow response frequency, strong anti-interference ability, small response S11 reflection, and high transmission power.

[0030] Reference Figure 5 It can be seen that the hardness of the nano-twinned copper antenna (marked as twinned copper) of Example 1 is increased from 1.25 GPa to 2 GPa compared with the coarse-grained copper antenna (marked as coarse-grained copper) of Comparative Example 1, indicating that the preparation method used to obtain Example 1 is beneficial to improving the mechanical properties of the nano-twinned copper antenna in the nano-twinned copper patch antenna.

[0031] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A nano-twin copper patch antenna, characterized in that: The invention comprises a nano twin copper antenna, a dielectric substrate and a protective layer covering the nano twin copper antenna. The thickness of the nano twin copper antenna is 0.1-200 μm, and the organizational structure of the nano twin copper antenna comprises a nano twin structure.

2. The nano-twinned copper patch antenna according to claim 1, characterized in that: The twin spacing of the nano twin structure is 10-500nm.

3. The nano-twinned copper patch antenna according to claim 1, characterized in that: The dielectric constant of the dielectric substrate is 2-6 and the thickness is 0.5-2 mm.

4. The nano-twinned copper patch antenna according to claim 3, characterized in that: The dielectric substrate includes one or more of polyethylene terephthalate, polydimethylsiloxane and epoxy glass fiber composite material.

5. A method for preparing a nano-twinned copper patch antenna as claimed in claims 1-4, characterized in that: The following steps are involved: The copper anode and cathode plate are placed in an electroplating solution containing copper sulfate, an electrolyte channel is constructed between the cathode plate and the anode, a pulse current is applied through the anode and cathode plate, and the anode is moved relative to the cathode plate to perform electrodeposition on the cathode plate, thereby obtaining a copper antenna; The copper antenna is removed from the cathode plate, cleaned, and then fixed on a dielectric substrate, and then a protective layer covering the antenna is fixed on the dielectric substrate to obtain the copper patch antenna.

6. The method for preparing a nano-twinned copper patch antenna according to claim 5, characterized in that: The electroplating solution comprises copper sulfate, polyethylene glycol, an emulsifier and sodium chloride, wherein the concentration of the copper sulfate is 0.1-1 mol / L, the concentration of the polyethylene glycol is 0.05-0.1 g / L, the concentration of the emulsifier is 0.05-0.1 g / L, and the concentration of the sodium chloride is 0-100 mg / L.

7. The method for preparing a nano-twinned copper patch antenna according to claim 6, characterized in that: The electroplating solution also includes a brightener, a leveler and a dispersant. The concentration of the brightener is 0.01-0.1 g / L, the concentration of the leveler is 0.01-0.1 g / L, and the concentration of the dispersant is 0.01-0.1 g / L.

8. The method for preparing a nano-twinned copper patch antenna according to claim 6, characterized in that: The electrolyte also includes an oxidant, which is 27.5-35wt% hydrogen peroxide, and the added amount is 1-10mL / L.

9. The method for preparing a nano-twinned copper patch antenna according to claim 5, characterized in that: The pH of the electroplating solution is not greater than 1.

10. The method for preparing a nano-twinned copper patch antenna according to claim 5, characterized in that: The voltage of the pulse current is 10-50V, and the current density is 30-200mA / cm 2 , the turn-on time is 10-50ms, and the turn-off time is 100-300ms.

Citation Information

Patent Citations

  • Nano twin crystal copper foil and preparation method thereof, circuit board and current collector

    CN114232037A

  • Nano twin crystal copper material with (110) orientation and preparation method thereof

    CN115341248A

  • Bondable device including a hydrophilic layer

    US9773741B1

  • Nanotwinned crystal copper microinductor, and preparation method therefor and application thereof

    WO2023151389A1